Establishment and Achievements of Drug and Therapeutic Committee at the Oncology-Based Hospital of Nepal - Ghimire, Bijesh Raj; Shrestha, Sunil; Adhikari, Baburam; Shrestha, Sudip (Indian Journal of Pharmacy Practice)
Background: Drug and Therapeutics Committees (DTCs) serve as an assembly place to join and bond with diverse stakeholders of hospitals to improve the utilization of the medicinal fortes. DTCs are a key inclusion to promote the rational use of medications. DTCs are, however, operative in only a limited number of hospitals in Nepal. DTC was begun at the oncology specialized hospital, Nepal Cancer Hospital and Research Center (NCHRC), a new cancer Hospital in Lalitpur district, Nepal to promote the rational use of medicines in July, 2016. The DTC has representatives from various departments of the hospital and the complete support from the hospital administration. The main objective of this study is to highlight the activities done and ongoing work of the DTCs of the hospital. The DTC has been engaged with preparing the hospital formulary. Pharmacovigilance and pre- and post-chemotherapy counseling practices have been occurring. Educational programs and training for different dimensions of staffs are frequently carried out and drug use in the hospital is sporadically observed. Fundamental encounters with respect to the working of DTC is empowering, however, there are still bunches of activities for the judicious utilization of the medication.
Keywords: Rational use of medicines; Drug and Therapeutic Committee; Pharmacist; Hospital Pharmacy; Medicines; Nepal.